ଆଶ୍ଚର୍ଯ୍ୟ ଚର୍ଯ୍ୟାଚୟ - Buddhist Saints (Odisha Sahitya Akademi Bhubaneswar, 1989)
Charyapada, though it is claimed by all eastern languages as their beginning, various indigenous Odia words and meters used ascertained it's language as proto-Odia. These Buddhist poems written by 84 Sidhacharyas during 7th to 9th century discovered by M. M. Harprasad Shastri from Nepal. Admits in the introduction of this text that one poets domicile happens to be Odisha and his song also is written in Odia language. Out of these Buddhist signs some are undoubtedly from Odisha namely Kanhupa, Sabaripa, Luipa and Sarahapa . The tradition Sahajayana and the place Uddiyan were situated in ancient Odisha. The language in which these Buddhist poems were composed is known as Sandhya Bhasha or Twilight language. Because of this all the languages of eastern India are claiming it is their proto form. But on the basis of the linguistic analysis both morphological and syntactic study explores its root in proto-Odia language.
Ascharjaya Charjyachaya
Keywords: Odia